Bioeconomic optimal exploitation of the demesal fisheries in northwest Peninsular Malaysia - Tai, Shzee Yew (Universiti Putra Malaysia, 1994)
Fisheries Management involves the choice of appropriate regulatory schemes and determining the level of exploitation such that optimal effects can be achieved. both from the biological and economic standpoints. In this study, an attempt is made to determine the bioeconomic optimal rate of exploitation of the demersal fisheries in the northwest Peninsular Malaysia. A bioeconomic model for the fishery is developed and estimated. Based on the empirical estimates of the model relationships, levels of fishing etTort. catches, biomass and resource rent for the open access, maximum sustainable yield. static maximum economic yield and dynamic maximum economic yield for. several discount rates are estimated. The results indicate that even though present rate of exploitation of the demersal fishery shows slight improvement compared to the open access level, the demersal stock is overfished biologically and economically at this rate. An important result is that tremendous improvement for the demersal fishery in NWPM can be achieved if fishing effort is reduced by 60 to 78 percent from the present level. This implies an urgent need to formulate appropriate effort reduction management policies for the fishery in order to derive maximum benefits from the fishery